Revisiting the modifiers: how should the evaluation and management of acute concussions differ in specific groups?. Issue 5 (11th March 2013) - Makdissi, Michael; Davis, Gavin; Jordan, Barry; Patricios, Jon; Purcell, Laura; Putukian, Margot
Abstract : Background: One of the key difficulties while managing concussion in sport is that there are few prognostic factors to reliably predict clinical outcome. The aims of the current paper are to review the evidence for concussion modifiers and to consider how the evaluation and management of concussion may differ in specific groups. Methods: A qualitative review of the literature on concussion was conducted with a focus on prognostic factors and specific groups including children, female athletes and elite versus non-elite players. PubMed, MEDLINE and SportsDiscus databases were reviewed. Results: The literature demonstrates that number and severity of symptoms and previous concussions are associated with prolonged recovery and/or increased risk of complications. Brief loss of consciousness (LOC) and/or impact seizures do not reliably predict outcomes following a concussion, although a cautious approach should be adopted in an athlete with prolonged LOC or impact seizures (ie, >1 min). Children generally take longer to recover from concussions and assessment batteries have yet to be validated in the younger age group. Currently, there are insufficient data on the influence of genetics and gender on outcomes following a concussion. Conclusions: Several modifiers are associated with prolonged recovery or increased risk of complications following a concussion and have important implications for management. Children with concussion should be managed conservatively, with an emphasis on return to learn as well as return to sport. In cases of concussions managed with limited resources (eg, non-elite players), a conservative approach should also be taken. There should be an emphasis on concussion education in all sports and at all levels, particularly in junior and community-based competitions.